Bahasa Inggirs - Salwa Salsabila; Rina Pudjiastuti; Levy Olivia Nur; Harfan Hian Ryanu; Bambang Setia Nugroho (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2023)
Massive MIMO Antenna Design results in a very large antenna size that hinders the design process. The arrangement of Massive MIMO Antennas which consists of many antenna elements is a challenge in the design process due to the limited capability of the simulation software and the complicated process. Thus, a scalability technique is used to predict the specification results produced by a Massive MIMO Antenna array with a certain configuration based on a simple MIMO Antenna array with a 2x2, 4x4, 8x8, 16x16 MIMO element configuration scheme, etc. exponential increments. This research will discuss the scaling process to predict the specifications of a Massive MIMO Antenna array. The designed MIMO antenna arrangement is based on the design of a rectangular antenna with a truncated corner and a circular antenna with an X slot for further design with various types of configurations that work at a frequency of 3.5 GHz.